(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This study uses Critical Discourse Analysis (CDA) to examine how scientific publications establish authority, reinforce ideologies, and marginalise alternative perspectives in global academic discourse. The analysis examines linguistic and rhetorical strategies like high modality, nominalisation, passive voice, citation practices, and metaphors in a purposive sample of peer-reviewed articles from high-impact journals in medicine, physics, and social sciences, using Fairclough, Van Dijk, and Foucault frameworks. A comparison of English and Uzbek literature shows how scientific writing normalises hegemonic paradigms, strengthens neoliberal and technoscientific ideologies, and marginalises non-Western and local epistemologies. Language maintains epistemic hierarchies and shapes knowledge generation, according to key findings. The study promotes egalitarian knowledge systems through reflective scientific writing, inclusive citation, and critical discourse involvement. This research illuminates the socio-political aspects of scientific communication, contributing to global knowledge economy issues on power, ideology, and inclusivity.